2022
DOI: 10.4253/wjge.v14.i7.443
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life after surgical and endoscopic management of severe acute pancreatitis: A systematic review

Abstract: BACKGROUND Treatment for severe acute severe pancreatitis (SAP) can significantly affect Health-related quality of life (HR-QoL). The effects of different treatment strategies such as endoscopic and surgical necrosectomy on HR-QoL in patients with SAP remain poorly investigated. AIM To critically appraise the available evidence on HR-QoL following surgical or endoscopic necrosectomy in patient with SAP. METHODS A literature search was perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…The endoscopic procedure re-introduces pancreatic fluid (PF) into the GI tract, preventing electrolytes and fluid loss compared to the MIS procedure, where PF is drained out of the body. According to the findings of a recent study about the quality of life after INP treatment, endoscopic treatment provides a higher overall quality of life in terms of the patient’s health when compared to the surgical method [ 9 ]. The endoscopic technique has been demonstrated to yield the same or comparable results across all of the most recent investigations.…”
Section: Discussionmentioning
confidence: 99%
“…The endoscopic procedure re-introduces pancreatic fluid (PF) into the GI tract, preventing electrolytes and fluid loss compared to the MIS procedure, where PF is drained out of the body. According to the findings of a recent study about the quality of life after INP treatment, endoscopic treatment provides a higher overall quality of life in terms of the patient’s health when compared to the surgical method [ 9 ]. The endoscopic technique has been demonstrated to yield the same or comparable results across all of the most recent investigations.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from short-term outcomes, studies have evaluated long-term patient-related outcome measures. A recent systematic review by Psaltis et al [ 127 ] in 2022 included 11 articles which assessed the quality of life (QOL) after endoscopic and/or surgical management of SAP[ 127 ]; literature was heterogenous which rendered inability for pooled analysis. However, the authors suggested that endoscopic management may confer better QOL compared to surgical management based on current literature.…”
Section: Management Of Non-mild Apmentioning
confidence: 99%
“…The development of therapeutic endoscopic ultrasound (EUS), as well as adequate and dedicated devices, has enabled EUS-guided drainage to become the preferred approach of encapsulated pancreatic collections (EPCs), including pancreatic pseudocysts and walled-off pancreatic necrosis (WON) [3][4][5]. At present, EUSguided drainage is associated with a high clinical efficacy -similar to surgical drainage -but associated with fewer adverse events, reduced morbidity and better quality of life after procedure [6]. While EUS-guided treatment remains a highly effective treatment, there is currently no consensus on the best stent to achieve adequate drainage.…”
Section: Introductionmentioning
confidence: 99%